Effectiveness and Efficiency of Ipomoea aquatica and Ludwigia adscendens as Phytoremediators in Home Industry Tofu Liquid Waste - Indrawati, Rinda; Prasetyo, Hamdani Dwi; Latuconsina, Husain (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2024)
Tofu industries that do not have processing facilities often dump their waste water into river bodies, so that it can pollute the water and the surrounding environment. One way to improve water quality resulting from tofu liquid waste is phytoremediation which utilizes aquatic plants. This research aims to determine the effectiveness and efficiency of water spinach (Ipomoea aquatica) and water spinach (Ludwigia adscendens) in reducing water quality in household tofu liquid waste. The method used was experimental using a Randomized Block Design (RAK) consisting of 5 treatments and 4 replications. Data analysis uses ANOVA PAST descriptively using graphs or diagrams. The research results show that water spinach plants are the most effective for reducing pH, temperature, TDS, TSS and BOD levels. This shows that in general aquatic plants are able to neutralize tofu liquid waste in the Jilu River and still comply with the quality standards of PP RI No. 22 of 2021 Class III, except for TSS levels.